On the importance of a connected hard-phase skeleton for the creep resistance of Mg alloys - Amberger, Dorothea; Eisenlohr, Philip; Göken, Mathias (Acta Materialia, 2012)
The low density of Mg alloys renders them attractive for lightweight constructions. However, creep resistance remains an important limitation of Mg alloys for, for example, automotive power train applications. To gain a more detailed understanding of the correlation between microstructure and creep properties in die-castable Mg alloys, AZ91 alloys with nominal additions of 0, 1, 3, and 5 mass% Ca and the commercial alloy MRI 230D have been investigated. Creep tests show an increase in creep strength with increasing Ca addition and increasing cooling rate. Scanning electron microscopy reveals that this is correlated with an increasing interconnectivity of the intermetallic phase skeleton (in addition to the effect of small precipitates within the extgreeka-Mg matrix found in the case of MRI 230D). A simple isostrain composite analysis illustrates that a more interconnected skeleton shields more load from the matrix. Precipitation hardening can additionally strengthen the matrix, and thus the combination of both design approaches results in the highest observed creep resistance.
WW1::943